Tunable Dielectric and Thermal Properties of Oxide Dielectrics via Substrate Biasing in Plasma-Enhanced Atomic Layer Deposition - Kim, Yoonjin; Kwon, Heungdong; Han, Hyun Soo; Kim, Hyo Jin K.; Kim, Brian S. Y.; Lee, Byung Chul; Lee, Joohyun; Asheghi, Mehdi; Prinz, Fritz B.; Goodson, Kenneth E.; Lim, Jongwoo; Sim, Uk; et al. (American Chemical Society, 2020)
The ability to control the properties of dielectric thin films on demand is of fundamental interest in nanoscale devices. Here, we modulate plasma characteristics at the surface of a substrate to tune both dielectric constant and thermal conductivity of amorphous thin films grown using plasma enhanced atomic layer deposition. Specifically, we apply a substrate bias ranging from 0 to similar to 117 V and demonstrate the systematic tunability of various material parameters of Al2O3. As a function of the substrate bias, we find a nonmonotonical evolution of intrinsic properties, including density, dielectric constant, and thermal conductivity. A key observation is that the maximum values in dielectric constant and effective thermal conductivity emerge at different substrate biases. The impact of density on both thermal conductivity and dielectric constant is further examined using a differential effective medium theory and the Clausius-Mossotti model, respectively. We find that the peak value in the dielectric constant deviates from the Clausius-Mossotti model, indicating the change of oxygen fraction in our thin films as a function of substrate bias. This finding suggests that the increased local strength of plasma sheath not only enhances material density but also controls the dynamics of microstructural defect formation beyond what is possible with conventional approaches. Based on our experimental observations and modeling, we further build a phenomenological relation between dielectric constant and thermal conductivity. Our results pave invaluable avenues for optimizing dielectric thin films at the atomic scale for a wide range of applications in nanoelectronics and energy devices.